Bibliometric Analysis in Astrophysics: Overview of Education, Religion, and Local Wisdom in 2016-2021* - Zainuddin; Surya Haryandi; Misbah; Mastuang; Mohd Ali Ibrahim; Emy Nur Juliana; Munawarah; Ma’rifah Hidayati (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
Astrophysics education is one of the subjects in the physics education study program which is also part of astronomy. Astrology is the structure and epistemology of Islamic law that studies the sun, moon, stars, and celestial bodies related to aspects of Islamic law. Indonesian Muslims cannot be separated from local wisdom which is the wealth of the Indonesian nation. This article intends to provide a comprehensive explanation through bibliometric analysis of literature on astrophysics education, religion, and local wisdom. Article searches are performed by Publish or Perish (PoP) software on the Google Scholar database. The search and sorting results found 23 of the 200 articles found in the 2016-2021* range. The results of data processing by PoP software are then edited through the Mendeley Desktop software. The editing results are then processed using VOSviewer software to obtain a visualization of the distribution pattern and data mapping. Broadly speaking, this research shows the projected direction of astrophysics education research if it is studied with religious content based on the Qur'an and local wisdom and its further development. The implications of this research can inspire researchers to study astrophysics education in universities with the content of the Qur'an and local wisdom so that studying science can help increase faith in God.